Interindividual and interoccasion variability of toxicokinetic parameters in population models - Silvia Selinski; Wolfgang Urfer (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 1998)
The determination of toxicokinetic parameters is an essential component in the risk assessment of potential harmful chemicals. It's a first step to analyse the processes which are involved in the development of DNA adducts and might therefore lead to the development of cancer. The complete research depends on investigations with animals in vivo and in vitro, so that a critical step is the extrapolation from experimental animals to the human organism. Besides the investigation of the interspecific differences, the intraspecific and the interoccasion variability have to be analysed to avoid serious errors in the determination of the human risk. The aim of extrapolation from one species to an other requires a characterisation of the interesting processes which is valid for the whole species, i.e. population mean parameters instead of sets of parameters for different individuals, occasions and concentrations of the interesting chemical. The theory of hierarchical models, basically the work of Racine-Poon et al. (1985, 1986, 1990), provides a procedure, which incorporates both, modelling of the variability structure and reduction of complexity in terms of estimates of population mean parameter vectors. This paper presents part of a strategy to determinate the processes of uptake, elimination, and metabolism of the gas ethylene, which is a natural body constituent and an important industrial chemical.
Keywords: 519; EM algorithm; two-compartment model; population model; Bayes estimates; toxicokinetics; nonlinear hierarchical model